Analyticity of thermo-elastic semigroups with coupled hinged/Neumann B.C. - Irena Lasiecka; Roberto Triggiani (Abstract and Applied Analysis)
We consider a thermo-elastic plate system where the elastic equation does not account for rotational forces. We select the case of hinged mechanical B.C. and Neumann thermal B.C., which are coupled on the boundary. We show that the corresponding s.c. contraction semigroup (on a natural energy space) is analytic and, hence, uniformly stable. Because of the boundary (high) coupling, this case of B.C. is not contained in, and is more challenging than, recent known cases of the literature [L-R.1], [L-L.1], [L-T.1].